Effect of endoscopic endonasal skull base surgery on snoring - Do Hyun Kim; Min Hyeong Lee; Jaeyoon Lee; Sung Won Kim (Laryngoscope Investigative Otolaryngology, 2020)
Abstract Background As the number of endoscopic skull base surgeries has increased, postoperative changes in quality of life require attention, including evaluation of whether snoring symptoms change. Objective To investigate the effect of endoscopic endonasal skull base surgery on snoring and nasal symptom scores. Methods Between February 2009 and September 2018, 510 patients underwent skull base tumor resection via an endoscopic endonasal approach and were included in this study. Nasal symptoms were scored using the Nasal Obstruction Symptoms Evaluation (NOSE) scale and snoring symptoms were subjectively scored from 0 to 10 by partners using a visual analog scale (VAS). Computational fluid dynamics (CFD) was employed for pilot patient analysis. Results A pituitary adenoma was the most common surgical pathology encountered over the past 10 years (81.6% of all tumors). The NOSE scores increased significantly after surgery (pre‐surgery, 3.28 ± 3.18; post‐surgery, 4.09 ± 3.61; P < .001). The snoring VAS score decreased significantly postoperatively (pre‐surgery, 2.91 ± 2.74; post‐surgery, 2.43 ± 2.45; P < .001). A positive correlation was apparent between the NOSE and snoring score changes (r = 0.374; P < .001). Conclusions Snoring improved after endoscopic endonasal skull base surgery, associated with changes in nasal symptoms. Level of Evidence 4.